PRECISION-BASED OPTIMIZATION OF PLUCKING HEIGHT FOR TEA SHOOT YIELD, QUALITY, AND SUSTAINABLE SHOOT GROWTH ACROSS DIFFERENT PRUNING YEARS - Gina Nur’aini Buchory; Erdiansyah Rezamela; Iftita Fitri (UIN Sunan Gunung Djati Bandung, 2026)
Plucking management is a critical factor in maintaining tea production, shoot quality, and next generation of shoot growth. Improper plucking practices, particularly excessive low plucking, can negatively affect plant health by slowing down the shoot growth cycle, reducing the availability of maintenance leaves, and ultimately leading to decreasing shoot yield. Therefore, the need for precision-based plucking height to sustain optimal vegetative growth and yield in each plucking year is needed to be understood. One potential solution is the implementation of precise plucking height which is expected to improve shoot regeneration, maintain plant health and plucking table, and also enhance sustainable productivity in tea plantations. This study was conducted from October to November 2024 at a Tea Plantation in Bandung Regency using a split-plot randomized complete block design consisting of two factors (4×4) with 3 replications. Pruning year as the main plot consisted of 1st year (T1), 2nd year (T2), 3rd year (T3), and 4th year (T4) after pruning. The subplot was plucking height with 0 cm (K0), 1 cm (K1), 2 cm (K2), and 3 cm (K3) pad. Parameters comprised shoot yield per plot (kg), plucking points/m², pekoe shoot percentage, remaining P+1 shoot percentage, remaining P+2 shoot percentage, remaining banjhi shoot percentage and fresh shoot quality were measured. Data were analyzed using Analysis of Variance (ANOVA) (p≤0.05) and followed by Duncan’s Multiple Range Test (p≤0.05) if there were significant differences. The highest fresh shoot yield per plot was obtained from the T4K0 combination (70.77 kg plot⁻¹). The highest percentage of remaining shoots P+1 was recorded in the T4K1 treatment (29%). The minimum percentage of remaining banjhi shoot was resulted from T1K2 combination (14%). Meanwhile, fresh shoot quality was highest in the T2K1 combination (78%), followed by T2K2 (75%).